Neighbor signals perceived by phytochrome B increase thermotolerance in Arabidopsis - Arico, Denise Soledad (2019)
Due to the preeminence of reductionist approaches, understanding of plant responses to combined stresses is limited. We speculated that light‐quality signals of neighboring vegetation might increase susceptibility to heat shocks because shade reduces tissue temperature and hence the likeness of heat shocks. In contrast, plants of Arabidopsis thaliana grown under low red/far‐red ratios typical of shade were less damaged by heat stress than plants grown under simulated sunlight. Neighbor signals reduce the activity of phytochrome B (phyB), increasing the abundance of PHYTOCHROME INTERACTING FACTORs (PIFs). The phyB mutant showed high tolerance to heat stress even under simulated sunlight and a pif multiple mutant showed low tolerance under simulated shade. phyB and red/far‐red ratio had no effects on seedlings acclimated with non‐stressful warm temperatures before the heat shock. The phyB mutant showed reduced expression of several fatty acid desaturase (FAD) genes, and less proportion of fully unsaturated fatty acids and electrolyte leakage of membranes exposed to heat shocks. Red‐light‐activated phyB also reduced thermotolerance of dark‐grown seedlings but not via changes in FADs expression and membrane stability. We propose that the reduced photosynthetic capacity linked to thermotolerant membranes would be less costly under shade, where the light input limits photosynthesis.